Volleyball learning media using method of teaching games for understanding adobe flash-based - Refatana Asri Fani; Pamuji Sukoco (Research and Social Study Institute, 2019)
The study aims at generating a product in the form of Volleyball learning materials CD with the valid and effective TGFU method for the junior high school students. The learning media has been developed by using the Adobe Flash CS 6 Professional. Then, within the conduct of the study, the Research and Development (R&D) Model proposed by Borg & Gall had been adopted with several modifications. Then, the results of the study show that the learning media belongs to the â€œVery Goodâ€ category according to the material expert validation with the mean score 4.38 and that the learning media belongs to the â€œVery Goodâ€ category according to the media expert validation with the mean score 4.23. Furthermore, the results of the limited experiment show that the learning media belongs to the â€œVery Goodâ€ category with the mean score 4.76. Similarly, the results of the expanded experiment show that the learning media belongs to the â€œVery Goodâ€ category with the mean score 4.75. In order to identify the quality and the effectiveness of the product, an operational test should be performed. The results of the operational test show that the pre-test mean score is 41.65 while the post-test mean score is 89.25. The mean score of the students has improved with the gap 47.60 points. Therefore, departing from the overall results, the TGFU method-based learning media has been valid and effective for implementation in the learning activities of Sports and Health Education for the Junior High School degree.